The Role of Community-Based Rehabilitation in the Mental Recovery of Populations in Middle Eastern Conflict Zones: An Outcome Analysis - Luthfiah Mawar; M. Agung Rahmadi; Rasil Hakim Hasibuan; Zahra Aliyah Verisah; Dwi Keisya Kurnia; Helsa Nasution; Nurzahara Sihombing; Andieni Pratiwi (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
This meta-analysis evaluates the effectiveness of Community-Based Rehabilitation (CBR) programs in promoting mental health recovery in communities affected by long-term conflict in the Middle East. Analyzing 47 studies with 12,487 participants published between 2000 and 2024, the research shows significant improvements in mental health, with a large aggregated effect size (g=0.83, 95% CI [0.76, 0.90]). Social support mechanisms were found to mediate 43% of the treatment effect. This study also highlights the importance of culturally adapted CBR, which demonstrated a 27% increase in effect size compared to non-adaptive interventions (g=0.92 vs. g=0.72, p<0.001). Additionally, peer support significantly improved the sustainability of outcomes (OR=2.14, 95% CI [1.87, 2.41]). These findings provide a deeper understanding of the specific factors that contribute to the success of CBR in conflict-affected regions and offer new insights into intervention strategies for mental health recovery.